VALIDITAS MEDIA GAMBAR DENGAN APLIKASI MOVIE MAKER PADA MATERI SISTEM PENCERNAAN MANUSIA UNTUK TINGKAT SMP (Universitas PGRI Sumatera Barat, 2016)
The result of research interviews with biology teacher at SMPN 2 Sungai Limau, Padang- Pariaman district revealed that, when the teacher explains the material in human digestive system, teachers only explain lessons using media board. Though these materials, demanding to know the structure of the digestive organs and the digestive process. In addition, the average value of students for the material is still below 65, while KKM. The KKM is 77. So that the material presented by the teacher cannot be understood by the students well. Besides this, materials contained in these schools is not sufficient for the number of pupils and students only have worksheets that are not in accordance with the applicable curriculum. The purpose of this study is to look at the validity of the media images with applications movie maker in human digestive system materials for junior level. This research is development research and the data processed by descriptive statistik. Results of this study was to test the validity of media images with applications movie maker in human digestive system materials for junior high school is very valid with the average of 89.75%. And concluded that the validity of the media image with movie maker app on the human digestive system materials for junior high schools categorized as very valid with a average is 89.75%.